Diglyceride-rich oils from glycerolysis of edible vegetable oils - Ferretti, Cristián Alejandro (2018)
The human metabolism of 1,3-diglyceride is believed to occurthrough a pathway that avoids re-synthesis of triglycerides and theconsequent fat deposit in the body tissues. The synthesis of healthyvegetable oils with reduced triglyceride content was investigated usingfood production-compatible MgO as basic catalyst. The partial conversionof the triglycerides present in commercial edible oils into diglycerideswas carried out by glycerolysis. After optimizing the reaction conditionssuch as temperature, glycerol/triglyceride ratio, and inert gas flowrate, triglyceride conversions of up to 70% were reached after 8h as wellas a product containing 54% of diglycerides, 67% of which is thehealthier 1,3-isomer.